2013
DOI: 10.1186/1756-6649-13-2
|View full text |Cite
|
Sign up to set email alerts
|

Dose mapping sensitivity to deformable registration uncertainties in fractionated radiotherapy – applied to prostate proton treatments

Abstract: BackgroundCalculation of accumulated dose in fractionated radiotherapy based on spatial mapping of the dose points generally requires deformable image registration (DIR). The accuracy of the accumulated dose thus depends heavily on the DIR quality. This motivates investigations of how the registration uncertainty influences dose planning objectives and treatment outcome predictions.A framework was developed where the dose mapping can be associated with a variable known uncertainty to simulate the DIR uncertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Unfortunately, DIR is a high dimensional nonconvex problem, whose performance depends on numerous parameters such as type of algorithm, its implementation and image modality and quality . If used to calculate dose accumulation, small registration errors can cause significant dose errors in high gradient regions as shown by Tilly and Saleh‐Sayah …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, DIR is a high dimensional nonconvex problem, whose performance depends on numerous parameters such as type of algorithm, its implementation and image modality and quality . If used to calculate dose accumulation, small registration errors can cause significant dose errors in high gradient regions as shown by Tilly and Saleh‐Sayah …”
Section: Introductionmentioning
confidence: 99%
“…Hence, some groups proposed methods based on inverse consistency metrics or related to the Jacobian of the deformation fields to assure the plausibility of the physical characteristic of DVFs for clinical implementation of dose warping. Others investigated mathematical models relating the dose‐warping uncertainties to DIR errors, while experimental evaluation of both DIR and dose‐warping have been carried out using deformable dosimetric gels . Even though some studies showed promising results, the problem of the management of dose‐warping uncertainties in clinical settings remains an open area of research and a matter of debate, and is outside the aim of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Validation of DIR is a key aspect, therefore some authors have been evaluating the accuracy of DIR and dose warping using manually annotated points and structures, 5,6,12,13 physical plausibility of the transformations, 14,15 and by developing deformable and virtual phantoms with known deformations. [16][17][18][19] Others focused on estimating the accuracy requirements for dose warping 20,21 or estimating its precision. [22][23][24][25] Monte Carlo methods have also been proposed to recalculate doses using a deformed grid (with deformed and irregular voxels), which still uses DIR but minimizes the errors associated with dose interpolation.…”
Section: Introductionmentioning
confidence: 99%
“…57 The variance of these dose distributions revealed the pattern of dose mapping uncertainty arising from DVF uncertainties. Tilly et al 140 created a different model, by sampling DIR errors at a sparse grid of control points which was then applied to the denser dose grid by means of 3-D cubic interpolation. They studied the impact of the dose mapping uncertainties on the radiobiological outcome metrics for spot scanned proton therapy of the prostate, concluding that an uncertainty of the dose to the 95% of the tumor volume (D 95% ) less than 3% and a tumor control probability uncertainty less than 2% would require a mean absolute DIR error better than 2.5 and 3.5 mm, respectively.…”
Section: B Automatic Strategies: Dvf-basedmentioning
confidence: 99%